2012
DOI: 10.1002/nme.4363
|View full text |Cite
|
Sign up to set email alerts
|

Conservative integration of rigid body motion by quaternion parameters with implicit constraints

Abstract: SUMMARY An angular momentum and energy‐conserving time integration algorithm for rigid body rotation is formulated in terms of the quaternion parameters and the corresponding four‐component conjugate momentum vector via Hamilton's equations. The introduction of an extended mass matrix leads to a symmetric set of eight state‐space equations of motion. The extra inertial parameter serves as a multiplier on the kinematic constraint, and it is demonstrated that convergence characteristics are improved by selecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…This is similar to the result in [3] when eliminating the single scalar normalization constraint from the four-component quaternion representation of rigid-body rotation.…”
Section: Elimination Of Lagrange Multiplierssupporting
confidence: 76%
See 2 more Smart Citations
“…This is similar to the result in [3] when eliminating the single scalar normalization constraint from the four-component quaternion representation of rigid-body rotation.…”
Section: Elimination Of Lagrange Multiplierssupporting
confidence: 76%
“…A fully conservative algorithm in terms of quaternion parameters can be obtained when the normalization condition is carried through the integration process via a Lagrange multiplier [2]. It was demonstrated in [3] that the rigid body dynamics problem can be formulated in such a way that the increment of the constraint is embedded in the kinematic evolution equation, and the Lagrange multiplier can be eliminated, leading to the introduction of a projection operator on the force potential gradient. An alternative formulation of the rigid body motion in terms of a set of convected base vectors has been introduced in [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top is represented as a cone with dimensions equivalent to those used in [16][17][18]. As illustrated in Figure 2, the parameters are height .…”
Section: Regular Precessionmentioning
confidence: 99%
“…[1]. The initial conditions correspond to those used in [16][17][18] Recently, regular precession top is detailed discussed by Krenk and Nielsen, in their researches about energy-momentum conserving integrations of rigid body dynamics [17,18]. They observed that the numerical integrations are of significant nutation error in simulation of regular precession, whether the integrations are implemented in terms of unit quaternion or convected base vectors.…”
Section: Regular Precessionmentioning
confidence: 99%